Long-Read Genome Sequence of the Sugar Beet Rhizosphere Mycoparasite Pythium oligandrum - Faure, Charlène; Veyssière, Marine; Boëlle, Betty; San Clemente, Hélène; Bouchez, Olivier; Lopez-Roques, Céline; Chaubet, Adeline; Martinez, Yves; Bezouška, Karel; Suchánek, Martin; Gaulin, Elodie; Rey, Thomas; et al. (G3, 2020)
Pythium oligandrum is a soil born free living oomycete able to parasitize fungi and oomycetes prey, including important plant and animals pathogens. Pythium oligandrum can colonize endophytically the root tissues of diverse plants where it induces plant defenses. Here we report the first long-read genome sequencing of a P. oligandrum strain sequenced by PacBio technology. Sequencing of genomic DNA loaded onto six SMRT cells permitted the acquisition of 913,728 total reads resulting in 112X genome coverage. The assembly and polishing of the genome sequence yielded180 contigs (N50 = 1.3 Mb; L50 = 12). The size of the genome assembly is 41.9 Mb with a longest contig of 2.7 Mb and 15,007 predicted protein-coding genes among which 95.25% were supported by RNAseq data, thus constituting a new Pythium genome reference. This data will facilitate genomic comparisons of Pythium species that are commensal, beneficial or pathogenic on plant, or parasitic on fungi and oomycete to identify key genetic determinants underpinning their diverse lifestyles. In addition comparison with plant pathogenic or zoopathogenic species will illuminate genomic adaptations for pathogenesis toward widely diverse hosts.
Keywords: proteom; rhizosféra; Proteome; genom; sekvenování transkriptomu; Beta vulgaris; Pythium; Genome; RNA-Seq; Rhizosphere